2019
DOI: 10.2139/ssrn.3397232
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Contribute: An Estimate of the Consequences of Non- and Underpayment of Self-Employment Taxes by Independent Contractors and On-Demand Workers on Social Security

Abstract: is to produce first-class research and forge a strong link between the academic community and decision-makers in the public and private sectors around an issue of critical importance to the nation's future. To achieve this mission, the Center sponsors a wide variety of research projects, transmits new findings to a broad audience, trains new scholars, and broadens access to valuable data sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…A key explanation for the decline is that the Bureau of Labor Statistics designed the CWS to capture data on nontraditional work that is a worker's main or sole source of income rather than a supplemental source of income (Bruckner & Hungerford 2019;Abraham & Houseman, 2019). Moreover, the survey only asked respondents to identify work done in the prior week, which "may fail to capture seasonal workers or workers that supplement their income" (U.S. Government Accountability Office, 2019, p. 3).…”
Section: Us Department Of Labor Bureau Of Labor Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…A key explanation for the decline is that the Bureau of Labor Statistics designed the CWS to capture data on nontraditional work that is a worker's main or sole source of income rather than a supplemental source of income (Bruckner & Hungerford 2019;Abraham & Houseman, 2019). Moreover, the survey only asked respondents to identify work done in the prior week, which "may fail to capture seasonal workers or workers that supplement their income" (U.S. Government Accountability Office, 2019, p. 3).…”
Section: Us Department Of Labor Bureau Of Labor Statisticsmentioning
confidence: 99%
“…In addition to analyzing multiple jobholding trends, SIPP data has been used to estimate populations of independent contractors and on-demand workers. For example, Bruckner and Hungerford (2019) 1). The education services/health care/social assistance industry was the home to largest percentage of both women and men who were multiple job holders: it attracted 40.7% of the women with multiple jobs and 16.7% of the men with multiple jobs (ibid., p. 6 figure 4).…”
Section: Us Census Bureaumentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from other countries confirm that the self-employed often underreport their earnings (Hurst, Li and Pugsley, 2010 [26] ; Bucci, 2019 [27] ). In the United States, a 2018 survey found that 32% of self-employed admittedly underreport their income for tax purposes (Bruckner and Hungerford, 2019 [28] ). Moreover, the inclination towards informality might be magnified when working with or through the internet platforms, especially if the platforms are based abroad and do not report any transaction data to Source: OECD domestic authorities.…”
Section: Income Validation Bargaining Power and Income Variabilitymentioning
confidence: 99%
“…A few countries introduced specific regulation to limit pension coverage gaps for selfemployed workers with only few major clients. While in Germany, self-employed persons who work predominantly for one client 28 and do not have employees have been mandatorily insured in the pension system since 1999, in Italy and Portugal the contributions of independent contractors relying on single contracts are now topped up by their clients. In addition, in Portugal if a self-employed worker depends significantly on one single client -the so-called ordering customer -the latter has to pay social security contributions for the self-employed.…”
Section: Policy Changesmentioning
confidence: 99%